Orthostatic Intolerance-Type Events Following Hip and Knee Arthroplasty: A Systematic Review and Meta-Analysis. (1st February 2023) - de Campos, Tarcisio F.; Vertzyas, Nick; Wolden, Mitch; Hewawasam, Deshitha; Douglas, Ben; McIllhatton, Christopher; Hili, Jessica; Molnar, Chloe; Solomon, Michael I.; Gass, Gregory C.; Mungovan, Sean F.
Abstract : Background: Orthostatic intolerance (OI)-type events following hip and knee arthroplasty increase the risk of falls, hospital length of stay, and health-care costs. There is a limited understanding of the incidence of and risk factors for OI-type events in patients during the acute hospital stay. Our aim was to systematically review the incidence of and risk factors for OI-type events during the acute hospital stay following hip and knee arthroplasty. Methods: A systematic review and meta-analysis of studies that investigated the incidence of and risk factors for OI-type events was undertaken. A comprehensive search was performed in MEDLINE, Embase, and CINAHL from their inception to October 2021. The methodological quality of identified studies was assessed using the modified version of the Quality in Prognosis Studies (QUIPS) tool. Results: Twenty-one studies (14, 055 patients) were included. The incidence was 2% to 52% for an OI event, 1% to 46% for orthostatic hypotension, and 0% to 18% for syncope/vasovagal events. Two studies reported female sex, high peak pain levels (>5 out of 10) during mobilization, postoperative use of gabapentin, and the absence of postoperative intravenous dexamethasone as risk factors. There was no consensus on the definition and assessment of an OI-type event. Conclusions: OI-type events are common during the acute hospital stay following hip and knee arthroplasty, and 4 risk factors have been reported for OI-type events. High-quality prospective cohort studies are required to systematically and reliably determine the incidence of and risk factors for OI-type events. Level of Evidence: Prognostic Level IV . See Instructions for Authors for a complete description of levels of evidence.